Budownictwo plecionkowe na tle porównawczym strefy Morza Bałtyckiego i Północnego - Gupieniec, Romana (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Houses built in a wattle technique belong to the oldest preserved house beginning systems originating from primitive shelters. Walls of houses made in a wattle technique are observed in various places in Europe. There is no doubt that because of wide occurrence of wattle houses they differed depending on the region, and ecological and economic conditions. I believe that traditional aspects could have played an important role here as well. Wattle technique was once used as a temporary solution conditioned by poverty, other time it was treated as a technique equal with remaining, widely practised construction technologies. As regards a variety of attitude to wattle constructions and reasons why they began to be used I would distinguish and compare three regions. The thirst region would cover the area of northern Poland and Polabia. The north of Poland would be characterised by small size wattle constructions raised because of impoverishment, partly because of people migrations and catastrophic events. Whereas in Polabia occur houses of more solid wattle construction constituting and included in more stable building system. Environmental conditions, economic arrangements or continuation of strongly rooted traditions are irrelevant here. In the second- north east region- wattle walls occurred rarely. They were used in household buildings only and they are not observed in dwelling houses. I believe that ecological conditions played an important role here. Domination of coniferous and mixed forests delivering large quantity of wood appeared useful in house building and this explains why wooden constructions were commonly used. Neither the aspects connected with catastrophic events, nor impoverishment and temporary depopulation were reflected in changes in the use of building systems. In this territory solid and earlier verified constructions were exceptionally preferred.